Community Theater and Resilience: The Case of the Greek Diasporic Community Theater in Brussels - Katerina Diakoumopoulou (Local Development & Society, 2022)
After 1981, with Greece’s accession into the European Economic Community (EEC), as today’s European Union (EU) was called at the time, the Greek diasporic phenomenon was transformed and the Greek theatrical mobility was mainly related to the recruitment of Greek officials to the EU institutions and organizations. For the next 40 years, the Greek Diasporic Community Theater (DCT) of Brussels has become a participatory field of integration and Greek troupes have begun to proliferate, influenced by the demographic, ideological, and socio-structural changes that have taken place both in Greece and Belgium in recent decades. The present paper studies and presents the causes of the artistic resilience of the Greek Diasporic Community Theater (DCT) in Brussels. The case of the Greek DCT in Brussels is such a unique case of DCT, which operates continuously and systematically from the early 1980s until today, flourishing and presenting unprecedented signs of resilience.